Dukungan Sosial, Religiusitas dan Stress pada Remaja di Lapas Anak Blitar - Dinatya Swastiani, Rr. Vivi Dinatya Swastiani; ., M Farid (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
The purpose of this study was to determine the relationship between socialsupport and religiosity with stress in adolescents who live in prisons son of Blitar.The subjects were 51 teenage boys who are undergoing punishment in prisons son ofBlitar. Data collection study conducted by DSI Scale (Daily Stress Inventory)developed by Brandey & Jones (1989), adolescent religiosity scale compiled byFarid (2004), and social support scale developed by the researchers.Nonparamentrik statistical analysis using the Spearman's Rho shows the correlationbetween social support and stress of 0201 and p = 0158 (p> 0.05); the correlationbetween religiosity and stress of 0182 and p = 0.200 (p> 0.05). These resultsindicate that there is no relationship between social support and religiosity withstress in adolescents Children's occupants Prison Blitar.Keywords : Stress, Social Support, Religiosity, Prison Kids, Teens